THE EFFECT OF PRICES ON THE SUSTAINABILITY OF RICE BUSINESSES IN THE CITY INDRAMAYU - Setiyarini, Dhiya Safira; Nursetiawati, Priya Dwi; Fajrina, Maya Oktavian; Febriyanti, Indri; Elipa; Wachdijono, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
Every business actor needs to be sustainable to reflects the certainty of income that can be used to maintain, develop and prosperity, family and employees. However, not all businesses can be sustainable because they are affected by several factors, including the price factor. This research aims to analyze effect price on the sustainability of the rice business in Indramayu City, West Java Province, along with the most applicable indicators explain the second condition variable. The research was carried out in April - May 2023 using a descriptive quantitative research design and survey methods. The number of samples was determined deliberately, namely 100 rice consumers in Indramayu City. Data analysis using the Structural Equation Model and research results conclude that prices have an effect positive and real to sustainability of the rice business. The indicator that can best explain the condition of price variables is “affordable” (0.76) and rice business sustainability is “making a profit” (0.71). The recommendation for rice business actors is to pay attention the prices rice where the price is strived to remain affordable for consumers.